Melanocytic lesions with blue naevus‐like (dendritic) morphology: an update with an emphasis on histopathological, immunophenotypic, and molecular features. Issue 3 (27th May 2021) - Cho, Woo Cheal; Prieto, Victor G; Aung, Phyu P
Abstract : An accurate diagnosis of melanocytic lesions requires a thorough histopathological evaluation accompanied by appropriate correlation with clinical examination findings. Although most melanocytic lesions can readily be classified as one of the defined diagnostic entities according to well‐established diagnostic criteria, a subset of melanocytic lesions, particularly those with blue naevus‐like (pigmented dendritic) morphology, have notoriously constituted an enduring challenge for pathologists. These lesions are rare and often show histological ambiguities, with features of both benignity and malignancy, thereby making accurate risk assessment and prediction of their biological behaviours difficult on histological grounds alone. Herein, we outline a practical and systematic approach for the diagnosis of melanocytic lesions with dendritic morphology, with a particular focus on histological and immunophenotypic features that help to distinguish one entity from another. In this review, we provide the most current knowledge on these melanocytic lesions in the literature and our experience with these rare entities, and we discuss the utility of molecular techniques as an ancillary tool, especially in histologically ambiguous and/or borderline lesions. Abstract :